2007
DOI: 10.1001/jama.297.17.1883
|View full text |Cite
|
Sign up to set email alerts
|

Levosimendan vs Dobutamine for Patients With Acute Decompensated Heart Failure

Abstract: A CUTE DECOMPENSATED HEART failure (ADHF) remains a common cause of hospitalization worldwide but it is not clear how patients admitted for clinical deterioration should be managed. Patients are generally treated with diuretics and vasodilators, while patients with evidence of peripheral hypoperfusion also may receive positive inotropes, usually dobutamine or milrinone. These positive inotropic agents improve hemodynamics and symptoms by increasing intracellular cyclic adenosine monophosphate within the failin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
527
7
41

Year Published

2009
2009
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 879 publications
(617 citation statements)
references
References 38 publications
23
527
7
41
Order By: Relevance
“…Results of recent major clinical trials in ADHF were not encouraging. 1,2 Hence, loop diuretics have remained the mainstay of ADHF treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Results of recent major clinical trials in ADHF were not encouraging. 1,2 Hence, loop diuretics have remained the mainstay of ADHF treatment.…”
Section: Introductionmentioning
confidence: 99%
“…In an updated meta‐analysis comprising six trials, we found no statistically significant difference in short‐term mortality,27, 28, 29, 30, 31, 32 long‐term mortality,27, 30, 31, 33, 34, 35 ischemic events,30, 34 acute kidney injury,31 dysrhythmias,30, 36 or hospital length‐of‐stay37 in patients with cardiogenic shock treated with dobutamine vs. levosimendan (Fig. 3, Fig.…”
Section: Resultsmentioning
confidence: 94%
“…Among these 59 surrogate endpoint trials that had a subsequent clinical endpoint trial, in 24 cases the clinical endpoint trial results validated the positive surrogate trials, while in 20 the subsequent clinical endpoint trial was negative (Table 3). 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50 A negative surrogate endpoint trial was less likely to be followed by a positive outcome trial and we identified only 3 such examples ( P =0.02, Figure 2). …”
Section: Resultsmentioning
confidence: 99%